Relative contributions of beta-cell function and tissue insulin sensitivity to fasting and postglucose-load glycemia - van Haeften, T. W.; Pimenta, W.; Mitrakou, A.; Korytkowski, M.; Jenssen, T.; Yki-Jarvinen, H.; Gerich, J. E. (W B Saunders Co, 2000)
We performed hyperglycemic clamps in 283 nondiabetic Caucasians and, with multiple linear regression, determined the contribution of beta-cell function and tissue insulin sensitivity to variations in glycemia and insulinemia during oral glucose tolerance tests (OGTTs). Impaired glucose tolerance (IGT) subjects had reduced insulin sensitivity(P < .02) and beta-cell function (P < .0001). Normal glucose tolerance (NGT) subjects with first-degree type 2 diabetic relatives had reduced first and second phase insulin secretion (both, P < .05), but normal insulin sensitivity(P = .37). beta-Cell function and insulin sensitivity accounted for one fourth of the variability in glucose tolerance. Fasting plasma glucose in subjects with NGT (n = 185) was a function of both phases of insulin secretion and of insulin sensitivity tall, P < .05), whereas, in IGT subjects (n = 98), it was a function of first phase insulin secretion and insulin sensitivity(P < .01). Two-hour glycemia was a function of second phase secretion and insulin sensitivity (P < .01). Fasting and 2-hour plasma insulin levels were determined by insulin sensitivity land glycemia) in NGT subjects (P < .001), but by second phase secretion in IGT (P < .001). We conclude that beta-cell function is reduced in subjects with IGT; glycemia and insulinemia are not regulated by the same mechanisms in IGT and NGT; insulin sensitivity does not contribute to insulinemia in IGT; family history of diabetes influences beta-cell function, but not insulin sensitivity in Caucasians. Copyright (C) 2000 by W.B. Saunders Company.